Pseudocholinesterase as a prognostic marker for liver disorder - Dhungana, Arun; Sinha, Jitendra Narayan; Sapkota, Saroj; Athokpam, Rajendra Singh (Journal of Kathmandu Medical College, 2015)
Background: Liver is the main source of pseudo cholinesterase. It is a non-specific cholinesterase found in the blood plasma and may be reduced in patients with advanced liver diseases. Measurement of serum pseudo cholinesterase activity serves as a sensitive indicator of synthetic capacity of the liver and can be used as a prognostic marker for carcinoma. Objective: To study pseudo cholinesterase activities in liver diseases. Method: A prospective study was conducted at College of Medical Sciences Teaching Hospital (CMS-TH), from May 2011 to May 2013 with 25 controls and 25 diagnosed cases each of carcinoma of liver, cirrhosis of liver, infective hepatitis and obstructive jaundice among both sexes of same age group attending medical outpatient and inpatient departments. Serum pseudo cholinesterase and other liver function tests were performed with semi-auto analyzer and Roche Hitachi 902 respectively. Results: Pseudo cholinesterase level was markedly decreased in carcinoma of liver (mean ± SD = 1369.48 ± 276.64 IU/L) followed by cirrhosis of liver (mean ± SD = 1735.16 ± 433.82 IU/L), infective hepatitis (mean ± SD = 3800.69 ± 764.17 IU/L), obstructive jaundice (mean ± SD = 5539 ± 791.05 IU/L) when compared with controls (mean ± SD = 6865.12 ± 928.41 IU/L). The difference in the means was statistically significant (p <0.001). Conclusion: There was significant decrease in pseudo holing esterase level in carcinoma of liver followed by cirrhosis of liver while less so in infective hepatitis. In obstructive jaundice the enzyme level was found to be decreased but higher than other liver diseases. The results indicated that with more severe liver cell destruction or cell degeneration, there was corresponding significant decrease in the level of pseudo cholinesterase, which could be used as diagnostic marker of liver disease. Journal of Kathmandu Medical College Vol. 3, No. 4, Issue 10, Oct.-Dec., 2014 Page: 131-135